2008
DOI: 10.1182/blood-2008-06-161919
|View full text |Cite
|
Sign up to set email alerts
|

Cell functions impaired by frataxin deficiency are restored by drug-mediated iron relocation

Abstract: Various human disorders are associated with misdistribution of iron within or across cells. Friedreich ataxia (FRDA), a deficiency in the mitochondrial ironchaperone frataxin, results in defective use of iron and its misdistribution between mitochondria and cytosol. We assessed the possibility of functionally correcting the cellular properties affected by frataxin deficiency with a siderophore capable of relocating iron and facilitating its metabolic use. Adding the chelator deferiprone at clinical concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 53 publications
1
100
0
Order By: Relevance
“…Deferiprone and deferasirox both access labile cardiac iron, and both appear to be superior to deferoxamine in this regard. 33 One possibility for the ejection fraction improvement seen with deferiprone may be that it prevents iron-related mitochondrial damage, 34 which could result in earlier restoration of mitochondrial function and ATP production, which are required for normal myocyte contraction. This accords with clinical experience that an improvement in ejection fraction may precede changes in T2*, with the former reflecting acute relief of toxicity and the latter measuring storage iron.…”
Section: Discussionmentioning
confidence: 99%
“…Deferiprone and deferasirox both access labile cardiac iron, and both appear to be superior to deferoxamine in this regard. 33 One possibility for the ejection fraction improvement seen with deferiprone may be that it prevents iron-related mitochondrial damage, 34 which could result in earlier restoration of mitochondrial function and ATP production, which are required for normal myocyte contraction. This accords with clinical experience that an improvement in ejection fraction may precede changes in T2*, with the former reflecting acute relief of toxicity and the latter measuring storage iron.…”
Section: Discussionmentioning
confidence: 99%
“…16 Maintenance of LVEF within the normal range is different to the response seen with deferiprone or combination therapy (deferiprone plus deferoxamine). The exact reason for this difference remains to be elucidated, although one explanation could be the greater access of the small molecule deferiprone to mitochondria, 17 where iron overload may suppress activity of the respiratory chain enzymes involved in the production of ATP. Interestingly, however, an increase in right ventricular ejection fraction measurements was seen with deferasirox, 18 but the relation of this change to the absence of left ventricular functional improvement is not currently understood.…”
mentioning
confidence: 99%
“…6,10 We have previously suggested that one explanation for this difference could be the greater access of deferiprone to mitochondria, 25 where iron overload may suppress activity of the respiratory chain enzymes involved in the production of adenosine triphosphate. 7,25,26 Deferasirox treatment for up to three years appeared to be well tolerated in patients with severe and mild-tomoderate myocardial iron overload. There were no deaths or drug-related serious AEs during 211 patient-years of deferasirox exposure and only one patient reported a serious cardiac AE.…”
mentioning
confidence: 99%